Neuroprotective Activity of Herbal Medicinal Products: A Review (International Journal of Current Research in Physiology and Pharmacology, 2022)
Plant-based drugs are among the earliest pharmaceuticals documented in even the most basic medical system's history. They are the most often used medicines due to their wide acceptance and general perception of their safer profile as compared to conventional drugs. Herbal medicines and products are gaining popularity around the world, not just as a caffeine-free alternative, but also as dietary supplements for low-calorie diets. In recent years, traditional medicine has gotten increased attention. Traditional medicine uses a range of herbs to cure neurodegenerative disorders such as Alzheimer's and other similar central nervous system issues. The term "neuroprotection" refers to strategies and systems for preventing neuronal injury in the central nervous system (CNS). Humans still have access to nature's medicines. Many important drugs are obtained from natural sources or based on the structural characteristics of naturally occurring substances, such as vincristine, artemisinin, and gentamicin. Traditional medicine has been documented to use a number of natural substances, usually plant extracts, for neuroprotective, memory-enhancing, and anti-aging objectives. Such plants include Panax ginseng, Ginkgo biloba, Bacopa monnieri, Curcuma longa, and Salvia officinalis. These plants were studied to see if the traditional claim was true, as well as to learn more about the mechanism through which they give neuroprotective advantages.
Keywords: Herbs, memory, neuroprotection, neuronal damage